Nuestras tiranías. Tocqueville acerca del despotismo democrático - González de Requena, Juan Antonio (2013)
“Our Tyrannies. Tocqueville on Democratic Despotism”. Although thelexicon of “tyranny” and “despotism” is subject to historical changes in meaning,we still keep on using those terms to refer to some types of illegitimate, unjust orindecent political regimes. So does Tocqueville, when he describes the new waysof despotism emerging from modern democratic revolution. In this article, weexplore the uses of “tyranny” and “despotism” in Tocqueville’s thought, and wealso try to discover the concrete models or social prototypes which could inspireTocqueville’s prognosis concerning a tutelary democratic despotism.